Skema Lokalisasi Posisi Node Terdistribusi pada Lingkungan Free Space Path Loss - Aries Pratiarso; Adam Surya Putra; Prima Kristalina; Amang Sudarsono; Mike Yuliana; I Gede Puja Astawa (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
A wireless sensor network consists of interconnected nodes that exchange information and use shared resource in a wireless transmission medium. Sensor nodes are randomly deployed in observation area in static or moving term. During this situation, the position of each sensor nodes is required to be known to monitor the circumstances around the node according to the information collected by sensor. Localization is the process to determine the position of nodes. This process could be done in centralized or distributed manner. In this paper, a distributed localization mechanism is proposed, where the calculation of node position is carried out on the node itself. Trilateration method is employed to calculate the position of node based on estimated distance measured by Received Signal Strength Indicator (RSSI) technique using Zigbee module in Free-Space Path Loss (FSPL) outdoor area. The experiment result shows that, based on log-normal shadowing model, the path loss coefficient for observation area is 2.5443, whereas average estimated position error from three different measured nodes are 23.504 m, 17.369 m, and 17.95 m respectively. Each node needs 2.73 second to undertake localization process completely.